Pengaruh Good Corporate Governance Terhadap Kinerja Keuangan Perusahaan Sektor Pertanian Yang Terdaftar di Index Saham Syariah Indonesia (ISSI) Periode Tahun 2017-2021 - Sakdiah, Halimatu; Nurlaila, Nurlaila; Inayah, Nurul (Journal of Student Development Informatics Management (JoSDIM), 2024)
This research aims to determine the effect of good corporate governance on financial performance. GCG is very important to implement in every company. This is important because the existence of GCG shows that management and shareholders are serious about building an open and accountable company together. Companies are not only responsible to shareholders, but also to their employees, the government and the community around the company. This type of research uses quantitative methods with descriptive statistical research characteristics. The methodology used is documentation and literature study methods. The data used in this research is secondary data, namely financial reports. Data processing in this research uses the SPSS 20 program. In this research, Good Corporate Governance will be proxied by three variables, namely managerial ownership, institutional ownership and audit committee, where this indicator is an important organ. Based on the research results, it shows that partially managerial ownership has a negative effect on financial performance with a significance of 0.216 and a calculated t value < t table (1.269 < 1.706). Institutional ownership has a positive effect on financial performance with a significance of 0.409 and a calculated t value > t table (1.793 > 1.706). The audit committee has a positive effect on financial performance with a significance of 0.40 and a calculated t value > t table (1.751 > 1.706. The coefficient of determination test results show that the Adjusted R Squared value is 21.6%, while the remaining 78.4% can be explained by other factors.